Assesment of the Use of Antibiotics in Patients Pneumonia Inpatients in Sultan Agung RSI Semarang with Method ATC/DDD - Wahyudi, Andrey; Pertiwi, Sulih (STIKES Telogorejo Semarang, 2022)
Pneumonia is an acute infectious disease that attacks the lung tissue, caused by viruses, bacteria, fungi and parasites that cause inflammation of the lung parenchyma and accumulation of inflammation in the respiratory tract. One of the treatments for pneumonia is antibiotics. It is necessary to control antibiotic resistance by evaluating antibiotics. This study purposed to evaluating the profile of antibiotic used in quantitative method to pneumonia patients at RSI Sultan Agung Semarang which was calculated using the ATC/DDD method. This research conducted retrospective cohort with cross sectional design. The sampling technique was used total sampling on 34 Pneumonia inpatients obtained from patient medical record. Subssquently, patient data analyzed by quantitatively using the ATC/DDD method. There are 5 types a single antibiotics used for pneumonia therapy, namely Levofloxacin (50%), Ceftriaxone (14.71%), Moxifloxacin (14.71%), Cefoperazone (11.76%), Meropenem (2.94%), and 2 types was used in combination, namely Loevofloxacin + Ciprofloxacin (2.94%) and Meropenem + Cefotaxime (2.94%). The value of DDD/100 days of hospitalization was 70.5 DDD/100 days of hospitalization with the highest antibiotic, namely Levofloxacin, of 40 DDD/100 days of hospitalization. Antibiotics included in the 90% segment were Levofloxacin (56.74%) and Moxifloxacin (18.71%). The most widely used antibiotic in pneumonia patients is Levofloxacin (50%). The total value of DDD/100 days of hospitalization for 1 period is 70.5 DDD/100 days of hospitalization. Antibiotics included in the 90% segment are Levofloxacin and Moxifloxacin.